Infection with Mycobacterium avium Differentially Regulates the Expression of Iron Transport Protein mRNA in Murine Peritoneal Macrophages - Zhong, Wangjian (American Society for Microbiology, 2001)
Iron is an important element for the growth of microorganisms as well as in the defense of the host by serving as a catalyst for the generation of free radicals via the Fenton/Haber-Weiss reactions. The iron transporter natural resistance-associated macrophage protein 1 (Nramp1) confers resistance to the growth of a variety of intracellular pathogens including Mycobacterium avium. Recently several other proteins that are involved in iron transport, including the highly homologous iron transporter Nramp2 and the transferrin receptor-associated protein HFE (hereditary hemochromatosis protein), have been described. The relationship of these proteins to host defense and to the growth of intracellular pathogens is not known. Here, we report that infection with M. avium differentially regulates mRNA expression of the proteins associated with iron transport in murine peritoneal macrophages. Both Nramp1 and Nramp2 mRNA levels increase following infection, while the expression of transferrin receptor mRNA decreases. The level of expression of HFE mRNA remains unchanged. The difference in the expression of the mRNA of these proteins following infection or cytokine stimulation suggests that they may play an important role in host defense by maintaining a delicate balance between iron availability for host defense and at the same time limiting iron availability for microbial growth.